Granulometric and oxidizable carbon fractions of soil organic matter in crop-livestock integration systems - Wanderlei Bieluczyk (Semina: Ciências Agrárias, 2017)
The identification of the labile and recalcitrant forms of soil organic matter (SOM) allows to rapidly define, or even predict if the management used favors increments or losses of carbon in the soil. Thus, the objective of this work was to assess the effects of different grazing intensities and soybean crops on the oxidizable and granulometric fractions of the SOM in a crop-livestock integration combined with no-tillage system (CLI-NTS), established in 2009 in the Goiás Federal University. The treatments consisted of three different pasture heights (0.25 m P25; 0.35 m P35; 0.45 m P45), and areas without grazing (AWG), and a native vegetation area of the Cerrado biome (NCA), adjacent to the experimental area, was evaluated as references and compared with the cultivated areas. Soil samples (Oxisol – USDA; typic distroferric Red Latosol – SiBCS) were collected in the layers 0.00-0.05; 0.05-0.10 0.10-0.20 and 0.20-0.40 m of each area, and arranged in a completely randomized experimental design with six replications. The soil total carbon was quanti¿ed (TC) by dry combustion. The SOM granulometry and oxidizable SOM were fractionated into particulate carbon (OCp), carbon bond with minerals (OCm) and four oxidizable fractions with increasing degrees of recalcitrance (F1<F2<F3<F4). These soil attributes were evaluated at two different times, representing the post-pasture cycle (PP) and post-soybean crop (PC) periods. The lower contents of total soil carbon (TC) were found in the F1 and F3 fractions of the area without grazing, suggesting that the crop-livestock integration increases the organic matter content in the soil surface layer regardless of the pasture height. The areas without grazing and with different pasture heights in CLI had similar contents of OCp and OCm due to the experiment short time of implementation (3 years). The fractionation of the oxidizable SOM was more sensitive in differentiating the treatments, showing that the higher intensity of grazing used (P25) provided a better balance of carbon accumulation between the SOM labile and recalcitrant fractions.